PENGARUH STRATEGI KONTRAK KOMPETENSI DAN KEMAMPUAN PENGANTAR ELEKTRO TEKNIK TERHADAP KOMPETENSI MAHASISWA JPTE FT UNIMED - Baharuddin, Baharuddin (TABULARASA, 2013)
This study aims to determine the competency gap of students: 1) the contract was given to learning komvensional competence, 2) which has the capability of high power electro introduction to low, and 3) the interaction between electrical engineering capabilities with the introduction of learning strategies. The research was conducted in the Department of PTE FT Unimed . The research method is experimental 2x2 factorial design. The study sample comprised 52 people sebayak two treatment classes. The treatments were learning in the form of contractual competence, and learning komvensional. Data analysis is Tekinik Anava two lanes . The results showed that: 1) learning strategies in the form of a contract providing student competence competence better than komvensional learning strategies in introductory electrical engineering course, 2) Students who have the ability to obtain high electro introductory competencies better value when compared to students with low proficiency, 3) An interaction between learning strategy and the introduction of electrical engineering skills in influencing student competence in introductory electrical engineering course .